2014
DOI: 10.2478/sjps-2014-0005
|View full text |Cite
|
Sign up to set email alerts
|

European Identity and its Relationship to National and Ethnic Identities among Younger and Older Members of Ethnic Minority Groups

Abstract: European Identity and its Relationship to National and Ethnic Identities among Younger and Older Members of Ethnic Minority Groups. European identity is neither a new phenomenon nor a new concept. Yet, after almost three decades of research, this area is characterized by a wide variety of concepts and little empirical evidence. Existing studies in the area propose homogeneous concepts of societies and often disregard European identity among ethnic minorities and non-citizens. This paper addresses the gap in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Machacek (2011) found that young people from the Hungarian minority in Slovakia have more positive attitudes toward Europe and the ED than older age groups. Waechter and Samoilova (2014) show that among different ethnic minorities across eight countries, adults, unlike young people, consider their national identity more important than European identity. However, in only three minority groups was the difference in identification with Europe among age groups found to be significant.…”
Section: Introduction and Objectivesmentioning
confidence: 94%
“…Machacek (2011) found that young people from the Hungarian minority in Slovakia have more positive attitudes toward Europe and the ED than older age groups. Waechter and Samoilova (2014) show that among different ethnic minorities across eight countries, adults, unlike young people, consider their national identity more important than European identity. However, in only three minority groups was the difference in identification with Europe among age groups found to be significant.…”
Section: Introduction and Objectivesmentioning
confidence: 94%
“…Nor do they feel a strong attachment to CEE, but they feel closer to Europe than Hungarians in Slovakia. Other empirical studies found no correlation between ethnic and European identity (Waechter and Samoilova 2014).…”
Section: Identity and Identification In Normative And Empirical Perspmentioning
confidence: 85%